Typically Dutch - Kraan, Dirk-Jan (OECD Publishing, 2006)
This paper aims to identify a few features of institutions and policies in the Dutch public sector that can be characterised as "typically Dutch" and that, moreover, may be considered as worthy of further thought, or perhaps even as a source of inspiration, for countries that are presently thinking about the modernisation of their public sector. This aim implies two limitations that ought to be emphasised at the outset...